Magnetically modified microalgae and their applications - Safarik, Ivo; Prochazkova, Gita; Pospiskova, Kristyna; Branyik, Tomas (Critical reviews in biotechnology, 2016)
The majority of algal cells can interact with a wide range of nano- and microparticles. Upon interaction the modified cells usually maintain their viability and the presence of foreign material on their surfaces or in protoplasm can provide additional functionalities. Magnetic modification and labeling of microalgal biomass ensures a wide spectrum of biotechnological, bioanalytical and environmental applications. Different aspects of microalgal cell magnetic modification are covered in the review, followed by successful applications of magnetic algae. Modified cells can be employed during their harvesting and removal, applied in toxicity microscreening devices and also as efficient adsorbents of different types of xenobiotics.
Keywords: Adsorption; Harvesting algal cells; biotechnologie; magnetické jevy; Magnetic Phenomena; magnetic modification; Water Pollutants; magnetic separation; mikrořasy; Biotechnology; microalgae; Microalgae; látky znečišťující vodu; adsorpce; magnetic labeling